2019
DOI: 10.1002/bio.3610
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pH and micellar systems on the sensitized photo‐oxidation of bovine serum albumin

Abstract: Photosensitized oxidation of bovine serum albumin (BSA), by using perinaphtenone as a sensitizer, has been studied at pH 7.4 and 11. The selected sensitizer does not present ground‐state complexation with BSA and ensures that the mechanism is mediated by O2(1△g). Strong dependence between BSA–O2(1△g) photo‐oxidation and the pH of the medium has been found. The relative oxygen uptake rate (v− △ O2) and the total quenching rate constant (kt) values are higher at pH 11 than pH 7.4. The enhancement in the alkaline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…In previous works carried out by our research group, we studied the O 2 ( 1 Δ g )-mediated photooxidation of bovine serum albumin and α-chymotrypsin proteins in reverse micellar systems (Reynoso 2008(Reynoso , 2019. In these investigations, it was observed that the reaction of biomolecules with the photogenerated species decreased markedly in the aforementioned system in comparison to the reaction in aqueous medium.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous works carried out by our research group, we studied the O 2 ( 1 Δ g )-mediated photooxidation of bovine serum albumin and α-chymotrypsin proteins in reverse micellar systems (Reynoso 2008(Reynoso , 2019. In these investigations, it was observed that the reaction of biomolecules with the photogenerated species decreased markedly in the aforementioned system in comparison to the reaction in aqueous medium.…”
Section: Resultsmentioning
confidence: 99%
“…Particularly, RMs have been shown to provide a certain degree of protection against protein sensitized photo-oxidations (Reynoso et al 2008(Reynoso et al , 2019, as well as a difference in the catalytic capacity of multiple enzymes as compared with aqueous medium (Falcone et al 2004;Biasutti et al 2008;Moyano et al 2010).…”
Section: )mentioning
confidence: 99%